Spatio-temporal performance of major edible oilseeds in Andhra Pradesh: SPATIO-TEMPORAL PERFORMANCE OF MAJOR EDIBLE OILSEEDS IN ANDHRA PRADESH - I KRISHNA TEJA; S V RAMANA RAO; I BHAVANI DEVI; S V PRASAD; B RAVINDRA REDDY; PALADUGU PRAVEEN KUMAR (Journal of Oilseeds Research, 2021)
The current analysis examines the spatio-temporal performance of major edible oilseed crops viz., groundnut, sesame and sunflower in Andhra Pradesh using time series data from 1970-71 to 2018-19. The total period was divided into three sub-periods viz., Period I (1970-71 to 1985-86), Period II (1986-87 to 1999-2000) and Period III (2000-01 to 2018-19). Agro-climatic zones, in which these crops were consistently grown, were selected and their performance was evaluated using compound annual growth rates and decomposition analysis. Growth of area and production of groundnut and sunflower exhibited frequent declined growth rates, particularlyin Period III, signifying the under performance of these crops. The performance of sesame was better vis-a-vis groundnut and sunflower. There was no significant decline in growth rates of yields, which could be partly attributed to efforts from the research community and government to increase the yield through various oilseeds development programmes. Although efforts were made towards increasing area, production and yield, the positive growth momentum of area and production could not be sustained. Shift of major oilseeds' cultivation towards competing crops, low profitability, unremunerative market prices, low farm level technical efficiency, increased costs of inputs, higher biotic and abiotic stresses etc., could be some of the reasons for this scenario. Location specific research with focus on hybrids and HYVs with high oil content, addressing the constraints to technology adoption, favourable price policies, enhancing capacityutilization of processing units, creatingmore efficient supply and value chains mayhelp in meeting the oil and oilseed requirements in the country.